Critical Closing Pressure Determined with a Model of Cerebrovascular Impedance. Issue 2 (February 2013) - Varsos, Georgios V; Richards, Hugh; Kasprowicz, Magdalena; Budohoski, Karol P; Brady, Ken M; Reinhard, Matthias; Avolio, Alberto; Smielewski, Peter; Pickard, John D; Czosnyka, Marek
Critical closing pressure (CCP) is the arterial blood pressure (ABP) at which brain vessels collapse and cerebral blood flow (CBF) ceases. Using the concept of impedance to CBF, CCP can be expressed with brain-monitoring parameters: cerebral perfusion pressure (CPP), ABP, blood flow velocity (FV), and heart rate. The novel multiparameter method (CCPm) was compared with traditional transcranial Doppler (TCD) calculations of CCP (CCP1). Digital recordings of ABP, intracranial pressure (ICP), and TCD-based FV from previously published studies of 29 New Zealand White rabbits were reanalyzed. Overall, CCP1 and CCPm showed correlation across wide ranges of ABP, ICP, and PaCO2 ( R = 0.93, P < 0.001). Three physiological perturbations were studied: increase in ICP ( n = 29) causing both CCP1 and CCPm to increase ( P < 0.001 for both); reduction of ABP ( n = 10) resulting in decrease of CCP1 ( P = 0.006) and CCPm ( P = 0.002); and controlled increase of PaCO2 ( n = 8) to hypercapnic levels, which decreased CCP1 and CCPm, albeit insignificantly ( P = 0.123 and P = 0.306 respectively), caused by a spontaneous significant increase in ABP ( P = 0.025). Multiparameter mathematical model of critical closing pressure explains the relationship of CCP on brain-monitoring variables, allowing the estimation of CCP during cases such as hypercapnia-induced hyperemia, where traditional calculations, like CCP1, often reach negative non-physiological values.